Establishing contest site mind-sets - Rushall, B. S. (Mental Skills Training for Sports, 1995)
How an athlete should act at a contest site is a frequently discussed topic, but one which has been subjected to little investigation. Most coaches have their personal recipe for what should be done. Some research has described what champion athletes do to prepare themselves for an important competition for the duration of the time at the contest site. This exercise describes those behaviors and activities as being a model for emulation.